Mucin-Based Biomimetic Patches for Dynamic Heart Repair: Auxetic Structures and Translational Challenges - Rishatani Gunasegaran; Rania Hussien Al-Ashwal; Norhana Jusoh; Muhammad Hanif Ramlee; Sadeq M. Al-Hazmy (Cardiovascular Engineering and Technology, 2026)
Purpose This scoping review examines strategies to improve adhesion and integration of epicardial patches within the dynamic and wet cardiac environment. It emphasizes mucin-based bioadhesives and auxetic designs as potential solutions for long-term tissue-conformal myocardial repair. Methods Approximately 150 peer-reviewed articles published between 2010 and 2024 were identified through a structured literature search conducted across PubMed, Scopus, and Web of Science. The studies cover adhesive biomaterials, structural patch designs, and epicardial tissue repair approaches were screened and thematically synthesized to map current advances, limitations, and translational gaps. Results Commercially available epicardial patches fail to maintain adhesion under cyclic loading and fluid-rich conditions. Among bioadhesives, mucin demonstrates promising wet adhesion, viscoelasticity, and biocompatibility. Nonetheless, its translation is limited by batch-to-batch variability, purification challenges, and potential immunogenicity. Dopamine-, hyaluronic acid-, and alginate-based adhesives provide alternatives but remain constrained by oxidative instability, limitted long-term durability, or inadequate mechanical performance. Structural innovations such as auxetic geometries improve patch flexibility, strain distribution, and conformability compared with multilayered or microneedle-based strategies. However, challenges related to fabrication, sterilization, scalability and potential interference of cardiac anatomy andphysiology require further investigation. Conclusions The synergistic integration of mucin-based adhesives with auxetic designs presents a compelling pathway toward durable, biocompatible, and tissue-conformal cardiac patches. Addressing manufacturing scalability, reproducibility, and immunological safety will be critical to advancing these concepts toward clinical applications.

Colocalization of Coronary Plaque with Wall Shear Stress in Myocardial Bridge Patients - Muhammad Owais Khan; Takeshi Nishi; Shinji Imura; Jongmin Seo; Hanjay Wang; Yasuhiro Honda; Koen Nieman; Ian S. Rogers; Jennifer A. Tremmel; Jack Boyd; Ingela Schnittger; Alison Marsden (Cardiovascular Engineering and Technology, 2022)

During Early VF in Rabbit Hearts, His Bundle Pacing is Less Effective Than Working Myocardial Pacing in Modulating Left Ventricular Activation Rates - Ankur R. Shah; Muhammad S. Khan; Matthias Lange; Annie M. Hirahara; Gregory Stoddard; Ravi Ranjan; Derek J. Dosdall (Cardiovascular Engineering and Technology, 2022)

Preparation of Cell-Seeded Heart Patch In Vitro; Co-Culture of Adipose-Derived Mesenchymal Stem Cell and Cardiomyocytes in Amnion Bilayer Patch - Normalina Sandora; Muhammad Arza Putra; Pribadi Wiranda Busro; Ardiansyah; Chaidar Muttaqin; William Makdinata; Nur Amalina Fitria; Tyas Rahmah Kusuma (Cardiovascular Engineering and Technology, 2022)

Multiple Aneurysms AnaTomy CHallenge 2018 (MATCH): Phase I: Segmentation - Philipp Berg; Samuel Voß; Sylvia Saalfeld; Gábor Janiga; Aslak W. Bergersen; Kristian Valen-Sendstad; Jan Bruening; Leonid Goubergrits; Andreas Spuler; Nicole M. Cancelliere; David A. Steinman; Vitor M. Pereira; et al. (Cardiovascular Engineering and Technology, 2018)

Regenerative Stem Cell Therapy Optimization via Tissue Engineering in Heart Failure with Reduced Ejection Fraction - Mehmet Alkan; Raef Madanieh; Niel N. Shah; Muhammad U. Dogar; Parin N. Shah; Sameera Ishtiaq; Constantine E. Kosmas; Timothy J. Vittorio (Cardiovascular Engineering and Technology, 2017)

A Novel Idea to Improve Cardiac Output of Mechanical Circulatory Support Devices by Optimizing Kinetic Energy Transfer Available in Forward Moving Aortic Blood Flow - Muhammad B. Qureshi; Jacob Glower; Daniel L. Ewert; Steven C. Koenig (Cardiovascular Engineering and Technology, 2017)

Effect of Loss of Heart Rate Variability on T-Wave Heterogeneity and QT Variability in Heart Failure Patients: Implications in Ventricular Arrhythmogenesis - Sachin Nayyar; Muhammad A. Hasan; Kurt C. Roberts-Thomson; Thomas Sullivan; Mathias Baumert (Cardiovascular Engineering and Technology, 2017)